2022
DOI: 10.33423/jhetp.v22i10.5384
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Early University Dropout Intentions Questionnaire (EUDIQ-R)

Abstract: Since the implementation of the European Higher Education Area, university dropout rate has become consolidated as an indicator of quality, due to the negative impact it can have. However, there are not many validated instruments available to study it. In this context, the objective of this study was to validate a reduced version of the Early University Dropout Intentions Questionnaire (EUDIQ-R), based on a theoretical model derived from the main studies in this area and with reference to other instruments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Early University Dropout Intentions Questionnaire (EUDIQ-R) (Bernardo et al, 2022). 2022 2 Screening instrument for students at-risk of dropping out from Higher Education (Casanova et al, 2021).…”
Section: Studies (Id) Instrument Name Year Of Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Early University Dropout Intentions Questionnaire (EUDIQ-R) (Bernardo et al, 2022). 2022 2 Screening instrument for students at-risk of dropping out from Higher Education (Casanova et al, 2021).…”
Section: Studies (Id) Instrument Name Year Of Publicationmentioning
confidence: 99%
“…However, no literature reviews have been found that focus on instruments that measure dropout intention. While instruments created ad hoc to investigate university abandonment are common, they can lead to omitting important factors, limiting the results and failing to provide a comprehensive vision of the phenomenon (Bernardo et al, 2022). Crucial for understanding and adequately addressing this problem is the access to effective instruments that can enable early detection (Casanova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The instrument used in this research consisted of two standardized questionnaires. First, the Early University Dropout Intentions Questionnaire (EUDIQ-R; Bernardo et al, 2022a). This questionnaire is composed by thirteen items grouped into three factors: satisfaction, social adaptation, and self-regulation strategies.…”
Section: Instrumentmentioning
confidence: 99%